Juridical Analysis on Role & Responsibility of Land Office in Multiple Land Certificates - Mochamad Amin; Amin Purnawan; Djauhari Djauhari (Sultan Agung Notary Law Review, 2021)
The imbalance between the supply of land and the need for land can lead to various land disputes, including the emergence of cases of double certificates. The Basic Agrarian Law lays the foundation for realizing legal certainty and legal protection for all Indonesian people. According to Article 19 of the UUPA Number 5 of 1960 which was followed up with Article 3 letter a of Government Regulation Number 24 of 1997 concerning the Purpose of Land Registration. In Indonesia, the institution that has a close relationship with land is the National Land Agency or BPN which has the task of carrying out government duties in the land sector in accordance with the provisions of the legislation. The objectives of this research are, one to find out and analyze the causes of the occurrence of double land certificates at the Land Office, two to identify and analyze the responsibilities of the Land Office in the case of multiple land certificates, three to identify and analyze the obstacles and solutions to the responsibilities of the Land Office in the completion of double land certificates. The approach method used in this research is empirical juridical, namely analyzing the problem by combining legal materials which are secondary data with primary data obtained in the field. The research specifications in this study are descriptive analytical. Types and sources of data, namely primary data are data. obtained from the field. secondary data, namely data obtained from or derived from library materials, data collection techniques with interviews, literature studies, document studies. Then the author analyzes qualitatively which is then presented descriptively.